ANALISA JAMUR Candida albicans PADA SWAB MUKOSA MULUT PEROKOK AKTIF DI LUBUK BUAYA - Anggun Sophia Sophia; Suraini (Department of Biology, Faculty of Mathematics and Natural Sciences, Hasanuddin University, 2023)
Candida albicans is a fungus found in the oral cavity which will cause abnormalities if thare are risk factors. Risk factors may increase growth of Candida albicans colonies and promote fungal invasion It infiltrates networks, forms colonies and grievances. One of the risk factors for Candida albicans proliferation smoking. The purpose study this for know analysis type Candida albicans with a mucosal swab mouth smoker Active in Lubuk Buaya Padang. Study this use types of analytical studies observant and approach Cross section. Collect data local residents under Smoking active, prompt willingness aspiring respondents. A mucosal swab was taken mouth and fill in informed consent. test end and SDA culture and exams in a way Visual inspection in a way microscopic and Gram stain and coloring Lactophenol Cotton blue (LPCB) and genital tract examination. Direct testing of 20 respondents revealed that 65% of the samples had Candida albicans colonies growing and non- Candida albicans growing 35 % too . Based on smoking duration, those who smoked for less than 3 years were found to be positive Candida albican 50 % tested positive for Candida albicans over 3 years 15%. Based on the number of cigarettes smoked, those who smoked less than 10 cigarettes per day were Candida albicans positive more than 25% and more than 10 cigarettes per day were positive for Candida albican A whopping 40 %. Based on tooth brushing behavior, those who brushed once were Candida albicans positive 10% were positive for Candida , 55 % and twice daily. Based on complaints with complaints that tested positive for Candida albican Up to 10% and up to 60 % of coffee/ tea drinkers were found to be Candida albicans positive and no coffee/ tea intake obtained positive Candida albicans 5 %. The study concluded that 65 % of the 20 samples were infected with Candida albicans 35% are non candida albicans.